LEGAL ASPECTS OF OPEN GOVERNMENT AT THE LOCAL LEVEL IN LATVIA - Skrastiņa, Una; Radzevičs, Juris (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
A municipality should provide its citizens' participation in self-government; in order to increase the public’s awareness of the activities of municipalities and their ability to participate in the discussions, measures must be taken. According to section 101 of the Constitution, every Latvian citizen has the right to participate in the national and local government’s activities. The forms of participation cannot be formal. Separate legal acts in various fields are adopted by the local authorities, and their institutions initiate public discussions. A too extensive and detailed list of participants increases bureaucratic barriers that restrict their participation. The aim of the research study is to analyse the legal aspects of open governance in a municipality in Latvia; through characterizing the problems, which most frequently have been stated in practice, to offer a deeper understanding of the matters addressed by the research study by searching for the best possible legislative regulation. The descriptive, dogmatic, historical, comparative and analytical research methods were used in this research. In order to achieve the aim, the following tasks were defined when analysing policy documents, legislation, conclusions of law scholars - to evaluate the concept of open governance partnership in the context of municipalities and legal aspects of information publicity and access as well as partnership implementation in a municipality.